Odpowiedzi

2009-11-23T21:25:39+01:00
A² + ab - 12b² dla a = ⅓ b = 1½
1/9 + 1/6 - 12/4 = 4/36 + 6/36 - 108/36= - 98/36 = 2 * 13/18
1 1 1
Najlepsza Odpowiedź!
2009-11-23T21:26:25+01:00
A² + ab - 12b² / - kreska ulamkowa

(⅓)² + ⅓*1½ - 12* (1½)² = 1/9 + 1/3* 3/2 - 12* (3/2)=
= 1/9 +1/2-12*9/4= 1/9+1/2-27 = 2/18 + 9/18 -27 = 11/18 -27 = - 26 i 7/18

tak mi sie wydaje, ale moze gdzies mam blad...
1 1 1
2009-11-23T21:26:05+01:00
A² + ab - 12b² dla a = ⅓ b = 1½

⅓²+⅓*1½-12*1½²=¹/₉+³/₆-27=⁴/₃₆+¹⁸/₃₆-27=²²/₃₆-27=26⁷/₁₈